2021
DOI: 10.1080/17439760.2021.1897868
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary mental wellbeing intervention for increasing flourishing: two experimental studies

Abstract: Positive Psychology Interventions (PPIs) have been shown to improve mental health, but little is known about their impact on the quantifiable experience of flourishing. Two experimental studies investigated whether the proportion of participants flourishing, assessed using the Huppert and So conceptual framework, could be increased through a 10-week online interdisciplinary intervention that combined strategies from positive psychology and lifestyle medicine. In Study 1 (n = 421), flourishing was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…The second main strength is the MHPI’s novel interdisciplinary nature that utilized multicomponent, evidenced-based strategies from the disciplines of lifestyle medicine and positive psychology. Using multicomponent strategies, rather than employing a single tactic, is also deemed to be more efficacious [ 56 , 71 , 82 ]. Third, the use of PSD principles in the intervention were both gender-responsive and age-sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second main strength is the MHPI’s novel interdisciplinary nature that utilized multicomponent, evidenced-based strategies from the disciplines of lifestyle medicine and positive psychology. Using multicomponent strategies, rather than employing a single tactic, is also deemed to be more efficacious [ 56 , 71 , 82 ]. Third, the use of PSD principles in the intervention were both gender-responsive and age-sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Both cohorts participated in an intervention referred to as the “The Live More Project” or “The Lift Project” [ 56 , 57 ]. The 10-week digital interdisciplinary MHPI used evidenced-based strategies from the disciplines of lifestyle medicine and positive psychology for improving mental health and well-being, as detailed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, it has been argued that multicomponent PPIs are more beneficial than single modality approaches (Morton et al, 2020;Przybylko et al, 2021). Hendriks et al (2019) conducted a systematic review and meta-analysis of 50 RCTs and concluded that Multicomponent PPIs (MPPIs) were efficacious, with a small to moderate effect on psychological well-being and a small effect on subjective well-being.…”
Section: Positive Psychology and Mental Healthmentioning
confidence: 99%
“…Accordingly, we argue that to optimize the effectiveness of mental health and well-being interventions, they should adopt an interdisciplinary approach, integrating evidence-based strategies from both the Positive Psychology and Lifestyle Medicine literature. The literature is scant in bringing these two disciplines together to improve mental health and well-being, although several studies (Morton et al, 2020;Przybylko et al, 2021;Renfrew et al, 2020) have suggested this interdisciplinary and multimodal approach may result in better outcomes than single modality interventions alone.…”
Section: A Call For Interdisciplinary Universal Mental Health Interventionsmentioning
confidence: 99%
“…We also examined the influence of a DMHPI on the experience of “flourishing” (Przybylko et al, 2021b ), which is a construct used to express a high level of human functioning. We found that the inclusion of text messaging support, or weekly videoconferencing support, had no additional benefit in the enhancement of flourishing.…”
Section: Human Supportmentioning
confidence: 99%